The thyroid hormone enhances mouse embryonic fibroblasts reprogramming to pluripotent stem cells: role of the nuclear receptor corepressor 1 - Contreras-Jurado, Constanza; Montero-Pedrazuela, Ana; Pérez, Raúl F.; Alemany, Susana; Fraga, Mario F.; Aranda, Ana (Frontiers in Endocrinology, 2023)
Pluripotent stem cells can be generated from somatic cells by the Yamanaka factors Oct4, Sox2, Klf4 and c-Myc. Here we show that the thyroid hormone triiodothyronine (T3) enhances reprogramming of mouse embryonic fibroblasts (MEFs) into induced pluripotent stem cells (iPSCs) by the Yamanaka factors. T3-induced iPSCs resemble embryonic stem cells in terms of the expression profile and DNA methylation pattern of pluripotency marker genes, and of their potential for embryod body formation and differentiation into the three major germ layers. T3 is able to increase reprogramming even though it increases expression of the cyclin kinase inhibitors p21 and p27, which are known to oppose This is a provisional file, not the final typeset article acquisition of pluripotency. Our results also indicate that the actions of T3 on reprogramming are mainly mediated by the thyroid hormone receptor b (TRb) and that T3 can enhance iPSC generation in the absence of c-Myc. The hormone cannot replace Oct4 on MEFs reprogramming, but in the presence of T3 is possible to obtain iPSCs, although with low efficiency, without exogenous Klf4. Furthermore, we also show here that depletion of the corepressor NCoR (or Nuclear Corepressor 1) with hairpin shRNA reduces MEFs reprogramming in the absence of the hormone and that iPSC generation by T3 and also by 9cis-retinoic acid, a well-known inducer of reprogramming, is strongly reduced in the absence of the corepressor. NCoR depletion also markedly antagonizes induction of pluripotency gene expression by both ligands. These results suggest that inclusion of T3 on reprogramming strategies has a potential use in enhancing the generation of functional iPSCs for studies of cell plasticity, disease and regenerative medicine.